1992
DOI: 10.1111/j.1432-1033.1992.tb16934.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a thermostable carboxypeptidase from the extreme thermophilic archaebacterium Sulfolobus solfataricus

Abstract: A carboxypeptidase was purified to electrophoretic homogeneity from the thermoacidophilic archaebacterium Sulfolobus solfataricus. Molecular masses assessed by SDS/PAGE and gel filtration were 42 kDa and 170 kDa, respectively, which points to a tetrameric structure for the molecule. An isoelectric point of 5.9 was also determined. The enzyme was proven to be a metalloprotease, as shown by the inhibitory effects exerted by EDTA and o-phenanthroline; furthermore, dialysis against EDTA led to a complete loss of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 43 publications
0
49
0
Order By: Relevance
“…One unit of arylesterase is defined as the amount of the enzyme required to liberate 1 mol of ␣-naphthol per min. Carboxylesterase activity was assessed by measuring the initial rate of hydrolysis of PNP esters containing unsubstituted fatty acids from butyrate (C 4 ) to palmitate (C 16 ) to yield p-nitrophenol at 405 nm and 60°C (45). The basal reaction mixture included 0.1 ml of freshly prepared and prewarmed PNP ester solution, 0.1 ml enzyme solution (8 g/ml), and 0.8 ml of prewarmed 100 mM sodium phosphate buffer (pH 7.0) containing sodium taurocholate (2 mg/ml) and gum arabic (1 mg/ml) as emulsifiers at 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…One unit of arylesterase is defined as the amount of the enzyme required to liberate 1 mol of ␣-naphthol per min. Carboxylesterase activity was assessed by measuring the initial rate of hydrolysis of PNP esters containing unsubstituted fatty acids from butyrate (C 4 ) to palmitate (C 16 ) to yield p-nitrophenol at 405 nm and 60°C (45). The basal reaction mixture included 0.1 ml of freshly prepared and prewarmed PNP ester solution, 0.1 ml enzyme solution (8 g/ml), and 0.8 ml of prewarmed 100 mM sodium phosphate buffer (pH 7.0) containing sodium taurocholate (2 mg/ml) and gum arabic (1 mg/ml) as emulsifiers at 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…The lack of any knowledge regarding archaebacterial carboxypeptidases led us to purify and characterize one such enzyme from Sulfolobus solfataricus (3), an extreme thermoacidophilic archaebacterium, isolated from volcanic hot springs, that grows optimally at 87ЊC (7). We found that this protein is a zinc metalloprotease endowed with a unique substrate specificity in that it could release basic, acidic, aromatic, and, to a lesser extent, aliphatic amino acids from artificial substrates.…”
mentioning
confidence: 99%
“…Many carboxypeptidases exhibiting broad substrate specificities have been reported. 22) On the basis of preferences for amino acids at the C-terminus, Penicillium janthinellum CP, 23) a member of the serine carboxypeptidases, and carboxypeptidase T from Thermoactinomyces sp. 24) cleaved the peptide bonds formed by basic and hydrophobic Cterminal amino acid residues, whereas carboxypeptidase A and carboxypeptidase C, and carboxypeptidase B and carboxypeptidase D exhibited strong preferences for hydrophobic and basic residues respectively.…”
Section: Biochemical Characterization Of Purified Tna1 Cpmentioning
confidence: 99%
“…Among them, the only three thermostable carboxypeptidase 1 from Thermus aquaticus (carboxypeptidase Taq), 2) T. thermophilus, 3) and the hyperthermophilic archaeon Pyrococcus furiosus 4) have been purified and characterized so far. Thermostable carboxypeptidase 1 is known to be very thermostable, with a temperature optimum of 80-100 C. 2,4) High optimum temperatures for activity have been reported for other carboxypeptidases purified from the bacterium Thermoactinomyces vulgaris 5) and the archaeon Sulfolobus solfataricus, 6) with temperature optima of 60 and 85 C respectively.…”
mentioning
confidence: 99%